Estimation of the core temperature control during ambient temperature changes and the influence of circadian rhythm and metabolic conditions in mice. (July 2015) - Tokizawa, Ken; Yoda, Tamae; Uchida, Yuki; Kanosue, Kazuyuki; Nagashima, Kei
Abstract: It has been speculated that the control of core temperature is modulated by physiological demands. We could not prove the modulation because we did not have a good method to evaluate the control. In the present study, the control of core temperature in mice was assessed by exposing them to various ambient temperatures ( T a ), and the influence of circadian rhythm and feeding condition was evaluated. Male ICR mice ( n =20) were placed in a box where T a was increased or decreased from 27 °C to 40 °C or to −4 °C (0.15 °C/min) at 0800 and 2000 (daytime and nighttime, respectively). Intra-abdominal temperature ( T core ) was monitored by telemetry. The relationship between T core and T a was assessed. The range of T a where T core was relatively stable (range of normothermia, RNT) and T core corresponding to the RNT median (regulated T core ) were estimated by model analysis. In fed mice, the regression slope within the RNT was smaller in the nighttime than in the daytime (0.02 and 0.06, respectively), and the regulated T core was higher in the nighttime than in the daytime (37.5 °C and 36.0 °C, respectively). In the fasted mice, the slope remained unchanged, and the regulated T core decreased in the nighttime (0.05 and 35.9 °C, respectively), while the slopes in the daytime became greater (0.13). Without the estimating individual thermoregulatory response such as metabolic heat production and skin vasodilation, the analysis of the T a – T core relationship could describe the character of the core temperature control. The present results show that the character of the system changes depending on time of day and feeding conditions. Highlights: We aimed to show the control of core temperature in free-moving mice. The influences of circadian rhythm and fasting on the control system were also assessed. Mice were exposed to ambient temperatures ranging from −4 °C to 39 °C We could show the control by the relationship between ambient and core temperatures. Circadian rhythm and fasting are factors that change the control system in mice.